Pembacaan Hermeneutik Puisi UhIbbuka Aksaru Karya Mahmud Darwisy: Kajian Semiotika Riffaterre - Hidayatun Ulfa (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
This article examines the meaning of poetry Uh} ibbuka Aks aru in the poetry anthology Al-Diwan: Al-'A'mal al-U <la> I work Mahmud Darwi sy> using Riffaterre semiotic studies. The purpose of this study is to find wholeness meaning (significance) in the poem. To produce the meaning of poetry, readings do heuristic and hermeneutic reading including where there is a matrix, model, variant, hipogram potential and actual hipogram. In this study, the authors attempt to derive meaning only through the hermeneutic reading only. The hermeneutic of reading produced a sense of poetry, the love of the homeland.